2004
DOI: 10.1111/j.1708-8240.2004.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness of Two 10% Carbamide Peroxide Tooth‐Bleaching Systems Using Spectrophotometric Measurements

Abstract: Mean deltaE values for Opalescence ranged from 5.03 to 8.92 and from 5.84 to 9.61 for Nite White. The most significant factor of the color change was b* followed by L* and a*. L* values were higher after bleaching, whereas values for both a* and b* decreased. There were no significant differences between the two systems examined (p < .05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 17 publications
5
18
2
1
Order By: Relevance
“…The nature of changes also corresponded to the ADA guidelines and literature: teeth became lighter (increase in DL*) and less chromatic (decrease in DC Ã ab ) after bleaching. [19][20][21]25 In addition, mean change in shade guide units for the VC system were the same as the instrumental findings, which supports the ADA recommendation that 1 ccu ¼ 1DE Ã ab ¼ 1 sgu. [19][20][21] The DE Ã ab values recorded for both with-and without light exceeded the 50:50% acceptability thresholds reported in other studies (DE Ã ab ¼ 2:7 26 and DE Ã ab ¼ 3:3 27 ).…”
Section: Ada Recommendations and Visual Judgments Of Color Differencessupporting
confidence: 75%
“…The nature of changes also corresponded to the ADA guidelines and literature: teeth became lighter (increase in DL*) and less chromatic (decrease in DC Ã ab ) after bleaching. [19][20][21]25 In addition, mean change in shade guide units for the VC system were the same as the instrumental findings, which supports the ADA recommendation that 1 ccu ¼ 1DE Ã ab ¼ 1 sgu. [19][20][21] The DE Ã ab values recorded for both with-and without light exceeded the 50:50% acceptability thresholds reported in other studies (DE Ã ab ¼ 2:7 26 and DE Ã ab ¼ 3:3 27 ).…”
Section: Ada Recommendations and Visual Judgments Of Color Differencessupporting
confidence: 75%
“…We also observed that, despite the lack of significant differences in luminescence among the groups, the highest numerical values for this characteristic were to be found in the blue LED group, followed by the halogen light group. These outcomes affirm the findings of other authors who likewise find evidence of an increase in a* and b* after dental bleaching (21), and they contrast with Ishikawa-Nagai et al (15), who observed an increase in luminosity L*. The alteration in luminosity represents how much the tooth lightened as a result of treatment, since this color dimension represents the amount of white incorporated to the hue.…”
Section: Discussionsupporting
confidence: 88%
“…The coordinates a* and b* approach zero for neutral colors (white, gray) and increase in magnitude for more saturated and intense colors. This system enables both the numerical definition of a color and the calculation of differences between two colors (14,15). To evaluate the color alteration of the teeth, we used an intraoral dental spectrophotometer, Vita EasyShade ® (VITAZahnfabrik H. Rauter Gmbh & Co. KG, Bad Säckingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A study using a spectrophotometer showed comparable L* and a*, but higher b*. 18 Studies performed with a digital camera system gave comparable results, except for a lower a*, as did a similar in vitro study using a spectroradiometer. 12,19,20 The importance of illumination geometry may be seen from the differences between the colours measured in our hemisphere set-up and our clinical simulation set-up.…”
Section: Discussionmentioning
confidence: 65%